Macrophage Polarization Favors Epithelial Repair During Acute Respiratory Distress Syndrome*. Issue 7 (July 2018) - Garnier, Marc; Gibelin, Aude; Mailleux, Arnaud A.; Leçon, Véronique; Hurtado-Nedelec, Margarita; Laschet, Jamila; Trebbia, Grégoire; Neuville, Mathilde; Tanaka, Sébastien; Crestani, Bruno; Dehoux, Monique; Quesnel, Christophe
Abstract : Objectives: Alveolar macrophage polarization and role on alveolar repair during human acute respiratory distress syndrome remain unclear. This study aimed to determine during human acute respiratory distress syndrome: the alveolar macrophage polarization, the effect of alveolar environment on macrophage polarization, and the role of polarized macrophages on epithelial repair. Design: Experimental ex vivo and in vitro investigations. Setting: Four ICUs in three teaching hospitals. Patients: Thirty-three patients with early moderate-to-severe acute respiratory distress syndrome were enrolled for assessment of the polarization of alveolar macrophages. Interventions: Polarization of acute respiratory distress syndrome macrophages was studied by flow cytometry and quantitative polymerase chain reaction. Modulation of macrophage polarization was studied in vitro using phenotypic and functional readouts. Macrophage effect on repair was studied using alveolar epithelial cells in wound healing models. Measurements and Main Results: Ex vivo, alveolar macrophages from early acute respiratory distress syndrome patients exhibited anti-inflammatory characteristics with high CD163 expression and interleukin-10 production. Accordingly, early acute respiratory distress syndrome-bronchoalveolar lavage fluid drives an acute respiratory distress syndrome–specific anti-inflammatory macrophage polarization in vitro, close to that induced by recombinant interleukin-10. Culture supernatants from macrophages polarized in vitro with acute respiratory distress syndrome-bronchoalveolar lavage fluid or interleukin-10 and ex vivo acute respiratory distress syndrome alveolar macrophages specifically promoted lung epithelial repair. Inhibition of the hepatocyte growth factor pathway in epithelial cells and hepatocyte growth factor production in macrophages both reversed this effect. Finally, hepatocyte growth factor and soluble form of CD163 concentrations expressed relatively to macrophage count were higher in bronchoalveolar lavage fluid from acute respiratory distress syndrome survivors. Conclusions: Early acute respiratory distress syndrome alveolar environment drives an anti-inflammatory macrophage polarization favoring epithelial repair through activation of the hepatocyte growth factor pathway. These results suggest that macrophage polarization may be an important step for epithelial repair and acute respiratory distress syndrome recovery. Abstract : Supplemental Digital Content is available in the text.